2007
DOI: 10.1645/ge-1025r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in Patients with Colorectal Cancer

Abstract: Parasitological examination of feces was carried out for 55 patients with diagnosed colorectal cancer before chemotherapy. Except for Cryptosporidium sp., no other intestinal parasites were found in the specimens; moreover, only the patients with watery diarrhea were Cryptosporidium sp.-positive by enzyme immunoassay. Prevalence of infection in the group of patients with diarrhea (23 persons) was 43.5%, whereas it was 18% for the entire group of patients under study. Coproantigens of this parasite were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
5
38
0
1
Order By: Relevance
“…An epidemiologic study in Poland reported a frequency of 18% of cryptosporidiosis in patients with colorectal cancer (17). However, in this report it was unclear whether C. parvum behaved as a carcinogenesis factor or simply as an opportunistic agent whose development was enhanced by host immunosuppression.…”
mentioning
confidence: 78%
“…An epidemiologic study in Poland reported a frequency of 18% of cryptosporidiosis in patients with colorectal cancer (17). However, in this report it was unclear whether C. parvum behaved as a carcinogenesis factor or simply as an opportunistic agent whose development was enhanced by host immunosuppression.…”
mentioning
confidence: 78%
“…In addition, the high prevalence of Cryptosporidium infection in our patients suggests that these protozoaare widespread in our environment. This high prevalence of infections with these opportunistic parasites among patients with cancer may result from the patients' reduced immunity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intestinal Cryptosporidium parvum infection is not rare in people with advanced HIV infection, and the organism has been observed in malignant colon tissue. 19,[21][22][23][24][25][26][27] Using a mouse model, Sasahara et al demonstrated the loss of absorptive cells and goblet cells, and the apoptosis of intestinal epithelial cells following Cryptosporidium parvum infection. 28 This protozoan is usually an intracellular parasite of the small intestine epithelium.…”
Section: Discussionmentioning
confidence: 99%